Integrated photonics for high-precision optical sensors - Beck, Paul; Wynne, Laura C.; Iadanza, Simone; O'Faolain, Liam; Schulz, Sebastian A.; Banzer, Peter (2023 Conference on Lasers and Electro-Optics Europe and European Quantum Electronics Conference, CLEO/Europe-EQEC 2023, 2023)
Integrated photonics has gained growing attention in the last two decades, mainly due to its potential to increase the speed of data transfer and to shrink the footprint of integrated circuits (ICs). This lead to the rapid development of a huge variety of integrated optical components and compound devices such as on-chip light sources, optical modulators, detectors and many others [1]. The technology developed in this framework can also be of great use for the miniaturization and integration of optical sensors. Here, we present a high-precision displacement sensor based on a silicon-on-insulator platform. The core of the device is a cylindrical, all-integrated scatterer which is excited by a tightly focused vector beam. This excitation and the resulting directional coupling of light to the surrounding waveguides depends strongly on the position of the device with respect to the focused beam [2]. Recording the light coupled out of each of the waveguides with a CCD camera and employing a tailored calibration technique enables localization of the device with a resolution of λ/200. Fig. 1 demonstrates the working principle of the device by means of two exemplary camera images. The difference among the two images in terms of the light observed at the four outcouplers is caused by a relative displacement of ∆x = ∆y = 160nm.
CRIS-Team Scopus Importer:2024-12-16